Detection of organochlorine pesticide residues in black pepper and clove using tolidine paper - NARAYANAN, N GOPALAKRISRNAN, C S (Journal of Spices and Aromatic Crops, 1998)
A simple method was developed for the quick detection of organochlorine pesticide residues in black pepper and clove using tolidine paper, prepared by wetting filter paper strips in 2% orthotolidine in acetone, Colour development when exposed to sunlight, showed the presence of the pesticide residues, The lower limit to which it can be detected was also estimated using gas chromatography fitted with electron capture detector, The tolidine paper detection technique was quick, reproducible and easy to adopt for the detection of o~ganochlorine pesticides like benzene hexachloride, aldrin, endosulfan and dichloro diphenyl trichlro ethane also in black pepper and clove,